Comparing the Sexual and Mental Health of Justice-Involved Youth Across Gender and Sexual Orientation - Hsu, Kevin J. (Criminal justice review, 2022)
Justice-involved youth may experience unique sexual and mental health risks related to both their gender and sexual orientation. Although previous research has revealed important gender and sexual orientation differences in the sexual and mental health of justice-involved youth, no study has yet examined gender and sexual orientation differences simultaneously within the same sample. The present study addressed this gap in a sample of 347 probation-involved youth, 13–17 years old, recruited as part of a randomized controlled trial of PHAT Life, an HIV/STI, mental health, and substance use prevention program. On the one hand, female and non-heterosexual youth were less likely than male and heterosexual youth to report having ever had sex and to be considered high sexual risk. On the other hand, female youth were more likely than male youth to test positive for STIs and to report certain mental health problems, but non-heterosexual youth showed no difference from heterosexual youth. Finally, female non-heterosexual youth were more likely to report externalizing problems than youth of other gender and sexual orientation combinations. Findings highlight the need for prevention and intervention efforts that specifically target justice-involved youth who identify as female, non-heterosexual, or both.